Interaction in euro area sovereign bond markets during the financial crisis - David Cronin (Intereconomics, 2014)
Applying a t-DCC-GARCH model to daily spread data, four phases of interaction in euro area sovereign bond markets are identified between January 2008 and June 2013. The initial period (January-October 2008) is followed by a general rise in pairwise correlation values between November 2008 and late 2009/early 2010. Interaction then declines on a piecemeal basis up to early 2012. In autumn 2012, coinciding with the announcement of the Outright Monetary Transactions programme by the European Central Bank, there is evidence of some reengagement of bond markets with one another. Policy then seems to have had an influence on euro area sovereign bond market behaviour. While it can act to calm markets, policy may also be unduly influencing market dynamics and raising moral hazard issues.
Keywords: 330; Öffentliche Anleihe; Geldpolitik; ARCH-Modell; Schätzung; EU-Staaten